Multiple infections with Cardinium and two strains of Wolbachia in the spider mite Tetranychus phaselus Ehara: revealing new forces driving the spread of Wolbachia. - Dong-Xiao Zhao (PLoS ONE, 2013)
Cytoplasmic incompatibility (CI) has been proposed as a major mechanism by which certain strains of Wolbachia to invade and persist in host populations. However, mechanisms that underlie the invasion and persistence of non-CI strains are less well understood. Here, we established a spider mite Tetranychus phaselus population multiply infected by Cardinium as well as two distinct lineages of Wolbachia, designated wCon and wOri, to study the forces driving the spread of the non-CI strain of Wolbachia wOri. Interestingly, we found that wOri provided a longevity advantage to its female hosts under ideal conditions, making wOri stay longer in this population, and then being transmitted to more offspring. Furthermore, the lifespan of uninfected females was reduced when mated with multiple-infected males. As a result, the uninfected population is attenuated by the multiple-infected males. Thus, we infer that the host age effects of multiple infection may represent sufficient forces driving the spread of wOri through the host population.